The influence of online learning readiness on mathematics achievement with mathematics self-efficacy as an intervening variable - Hamidy, Anwaril; Maula, Ishmatul; Lam, Kee-Fui Turner (Al-Jabar: Jurnal Pendidikan Matematika, 2023)
Background: The impact of online learning during the pandemic on students' mathematics achievements is influenced by their preparedness and belief in their ability to learn mathematics. Students’ readiness is closely linked to their self-efficacy.Aim: This study aims to examine the influence of online learning readiness on mathematics achievement, with mathematics self-efficacy serving as a mediator.Method: The study adopted a quantitative exploratory correlational approach to statistically explore the relationships between variables. It involved 197 students from UIN Sultan Aji Muhammad Idris Samarinda, who were enrolled in mathematics courses and selected through convenience sampling. Data were collected using an online learning readiness questionnaire and a mathematics self-efficacy scale, with final semester grades indicating mathematics learning achievement. Path analysis was utilized for data analysis.Result: The findings reveal that both online learning readiness and mathematics self-efficacy have a partial and simultaneous effect on mathematics learning achievement. Additionally, online learning readiness influences mathematics self-efficacy. The Sobel test results indicate that mathematics self-efficacy mediates the relationship between online learning readiness and mathematics learning achievement, with a more dominant direct influence of online learning readiness on mathematics achievement.Conclusion: The study underscores the importance of a student-oriented approach in online learning, considering the significant role of online learning readiness and self-efficacy in enhancing mathematics learning achievement.